An Analysis of the Main Characters in the Novel Ayat-Ayat Cinta by Habiburrahman El Shirazy - Suparni, Suparni; Wahono, Wahono (Yayasan Kyadiren, 2024)
This research aims to analyze the character of the protagonist in the novel Ayat-Ayat Cinta by Habiburrahman El Shirazy. The study employs a descriptive qualitative method, in which the researcher re-reads the novel to identify and examine the main characteristics of the protagonist. This approach seeks to provide a comprehensive understanding of the protagonist’s character. The findings indicate that the protagonist exhibits several significant traits, including honesty, humility, and responsibility. Additionally, the protagonist demonstrates discipline, compassion for others, and a romantic nature. These attributes are portrayed consistently throughout the novel, offering a clear and detailed depiction of the character’s personality.